PERKEMBANGAN REOG CING PO LING PAGUYUBAN PONCO MANUNGGAL JATI DI DESA JATIREJO, KECAMATAN KALIGESING, KABUPATEN PURWOREJO - Sudrajat Dewandana; Katarina Indah Sulastuti (Greget, 2020)
The article entitled Development of Reog Cing Po Ling Paguyuban Ponco Manunggal Jati in Jatirejo Village, Kaligesing District, Purworejo Regency is trying to uncover two problems, namely: (1) how the form of the show Reog Cing Po Ling Paguyuban Ponco Manunggal Jati in Jatirejo Village, Kaligesing District, Purworejo Regency today.; and (2) how is the development of Reog Cing Po Ling Ponco Manunggal Jati Group in Jatirejo Village, Kaligesing District, Purworejo Regency from 2016-2019. The first problem was examined based on the form theory which explained that the form of the performance consists of interconnected elements including dance moves, floor patterns, dance music, makeup and clothing, property, time and place of performance. Meanwhile, to examine the second problem used development theory that the development is a process of re-processing based on elements of tradition and expansion of the introduction area in the form of a new look without reducing or eliminating the values of existing traditions so that it can be enjoyed by the wider community. This research is qualitative. The techniques or steps in this study include the stage of data collection, the stage of data analysis, and the stage of preparing the report. The results of this study showed that Reog Cing Po Ling Ponco Manunggal Jati was carried out communally with elements of the show arranged neatly. The development of Reog Cing Po Ling Paguyuban Ponco Manunggal Jati lies in the elements of the show and the expansion of the stage area. The development occurred due to the influence of factors both from inside and outside the reog Cing Po Ling art group. Internal factors that influence the development of Reog Cing Po Ling include creativity of art actors, management of organizational systems, and spirit of togetherness among art actors. While external factors such as local government, artists from outside, and the development of technology  Keywords: Reog Cing Po Ling Paguyuban Ponco Manunggal Jati, Form, Development.